Regulation of starch and lipid accumulation in a microalga Chlorella sorokiniana. (March 2015) - Li, Tingting; Gargouri, Mahmoud; Feng, Jie; Park, Jeong-Jin; Gao, Difeng; Miao, Chao; Dong, Tao; Gang, David R.; Chen, Shulin
Highlights: We clearly describes accumulation patterns of starch and lipids. Accumulation of starch and lipids depends on nitrogen status. The biosynthesis of starch and lipids benefits from active photosynthetic activity. Lipid synthesis is largely dependent on starch degradation. Conversion of other cellular components is involved in the lipid synthesis. Abstract: Microalgae have attracted growing attention due to their potential in biofuel feedstock production. However, current understanding of the regulatory mechanisms for lipid biosynthesis and storage in microalgae is still limited. This study revealed that the microalga Chlorella sorokiniana showed sequential accumulation of starch and lipids. When nitrogen was replete and/or depleted over a short period, starch was the predominant carbon storage form with basal levels of lipid accumulation. After prolonged nitrogen depletion, lipid accumulation increased considerably, which was partially due to starch degradation, as well as the turnover of primary metabolites. Lipid accumulation is also strongly dependent on the linear electron flow of photosynthesis, peaking at lower light intensities. Collectively, this study reveals a relatively clear regulation pattern of starch and lipid accumulation that is basically controlled by nitrogen levels. The mixotrophic growth of C. sorokiniana shows promise for biofuel production in terms of lipid accumulation in the final biomass.